(untitled) (Global Journal of Medical Research, 2020)
This research determined the relationship between sociodemographic and labor factors with the work-family conflict of the nursing team of a highly complex Clinical Hospital in Chile. Using an analytical cross-sectional design, in a sample of 187 members of the nursing team (Professional nurses, Nurses’ Aides and Service Assistants), distributed among the hospital services of Medical-Surgical, Emergency Unit and Pediatrics. A questionnaire was used for sociodemographic and labor characterization and the Work Family Interaction questionnaire (SWING). The data was processed using descriptive and inferential statistics with the SPSS program, version 15. The ethical aspects were safeguarded. The results showed that 87.2% of the nursing team is composed of women, aged 20-39 years, mainly Nursing Assistants (57.2%). The work-family conflict was related to having a relative dependent on their position (p = 0.02) and with the remuneration received (p = 0.02).